Effectiveness of Near-Infrared Light Photodynamic Therapy on Oral Cancer Cells - Mr Jinhao Cui; Dr Tomoharu Okamura; Dr Chihoko Ikeda; Dr Kazuya Tominaga; Dr Akio Tanaka (Elsevier, 2023)
Aim or Purpose: The purpose of this study is to obtain basic data for PDT of human squamous cell carcinoma cell line (HSC-3) using the photosensitizer (Ce6), up-conversion particle (UC) and laser with near-infrared light (long wavelength) in vitro and in vivo. Materials and Methods: After using MTT Assay to determine a relatively suitable concentration combination, HSC-3 cells were treated with PDT with Ce6 and UC. Cell death by Calcein AM assay, apoptosis by FITC-Annexin V assay, intracellular singlet oxygen (Si-DMA for Mitochondrial Singlet Oxygen Imaging) and reactive oxygen species (ROS Assay Kit-Highly Sensitive DCFH-DA) were examined. HSC-3 cells were injected into the right lingual border of BALB/c nu/nu nude mice (4-weeks-old, female) and treated with PDT after 2 weeks later, then thinly sliced specimens were observed with hematoxylin-eosin staining, apoptosis staining and immunohistochemical staining using anti- cytokeratin (CK)17 antibody. Results: PDT with 0.5ng/μL Ce6 and 0.1ng/μL UC inhibits the cell proliferation of HSC-3 (P<0.05). PDT leads to an increase of intracellular singlet oxygen and ROS amount and apoptosis has occurred (P<0.05). When PDT with Ce6 and UC was performed on the lingual border of nude mice, CK17 positive carcinoma foci were observed and a part of the foci composed of HSC-3 had disappeared, apoptosis was detected in other parts. Conclusions: These results suggest that PDT with long wavelength laser can inhibit the proliferation of cancer cells and lead them to apoptosis.